Genetic algorithm and anti-predatory swarm optimisation-based solutions for selective harmonic elimination in multilevel inverters. (19th April 2022) - Gopal, Yatindra; Panda, Kaibalya Prasad; Birla, Dinesh
The elimination of harmonics and need of a large number of switches in multilevel inverters (MLIs) have been the focus of research from the last few decades. This paper reports the analysis of a 1-ɸ 7-level cascaded multilevel inverter (CHB MLI) and a new reduced switch MLI (RS MLI) using genetic algorithm (GA) and anti-predatory particle swarm optimisation (APSO) technique. To improve the output voltage quality, switching angles are evaluated using the GA and APSO techniques. The pluses generated based on the switching angles are further used for controlling the MLI. A comparison with recently developed MLIs is conducted to confirm the merits of the developed RS MLI. MATLAB software is used for simulation of the both the topologies, i.e., 1-ɸ 7-level CHB MLI and a 7-level RS MLI. Theoretical results are finally verified by developing a prototype in the laboratory.